الحياة الثقافية في عهد الراحل هواري بومدين 1965-1978م - ليلى بدرينة; د/محمد علاق (جامعة عمار ثليجي بالاغواط, 2025)
ملخص بالعربيّة: عاشت الجزائر بعد الاستقلال تحديات كبيرة وحقائق تاريخيّة بقيت في الذاكرة الفرديّة والجماعيّة، وذلك ضمن أحداث أملتها الاتجاهات السياسيّة والإيديولوجيّة، وكان لتلك الأحداث والحقائق أثرا عميقا على المجتمع وبناء الهوية الثقافيّة. كما كان لصعود الرئيس هواري بومدين إلى السلطة والانقلاب السياسي عام 1965م دورا كبيرا في الحياة الثقافيّة، شهد من خلاله الواقع السياسي والاجتماعي والثقافي تغييرا واضحا، أسهم في ظهور مؤسسات ثقافيّة وفنيّة؛ كانت بمثابة مرآة عاكسة لأهداف الثورة الثقافيّة والزراعيّة، فعبرت عن مبادئ وقيم جديدة ومواقف بآلياتها عززت ورسخت الأفكار والهويّة الوطنيّة، فحظيت من خلالها الجزائر بمكانة مرموقة على المستوى المحلي والعالمي بالرغم من المشاكل والأزمات التي مرّت بها. كما أثّرت الثقافات الأجنبيّة على الثقافة الجزائريّة بشكل متباين ومختلف فتدعم الفنون الأدبية والشعريّة فتمكّن الأدباء من التعبير عن آرائهم واتّجاهاتهم وفق تلك التحوّلات الكبرى التي عرفها المجتمع. والجدير بالذكر أنّ فترة حكم الرئيس هواري بومدين عرفت تطوّرا كبيرا في مجال الثقافة والفنون، وذلك بفضل ما سخّرته الدّولة من إمكانات ووسائل اتّصال؛ بخصائصها كان لها دور في تصوير المشاهد وإبراز الوعي الثقافي، فصنعت هذه الوسائل القيم وعبّرت عن الهويّة والقوميّة، وكانت عاملا قويا لإثبات الذات والدفاع عن الحقوق. فسيّر الإعلام الجانب الثقافي تسييرا متميزا معززا الشخصيّة الجزائريّة، هو نضال ثقافي بإمكانياته وخبراته عكس ذلك التطوّر المستمر والجهود المبذولة من طرف الدولة. الكلمات المفتاحيّة: هوّاري بومدين- ثقافة- هويّة- مجتمع- انفتاح . Summary: After independence, Algeria experienced major challenges and historical realities that remained in individual and collective memory, as part of events dictated by political and ideological trends. These events and realities had a profound impact on society and the construction of cultural identity. The rise of President Houari Boumediene to power and the political coup of 1965 also played a major role in cultural life. Through these changes, the political, social, and cultural reality witnessed a clear change, contributing to the emergence of cultural and artistic institutions that served as a mirror reflecting the goals of the cultural and agricultural revolution. These institutions expressed new principles, values, and positions, and their mechanisms reinforced and consolidated ideas and national identity. Through these institutions, Algeria gained a prestigious position locally and internationally, despite the problems and crises it experienced. Foreign cultures also influenced Algerian culture in varying and diverse ways, supporting literary and poetic arts, enabling writers to express their opinions and attitudes in light of the major transformations that society experienced It is worth noting that the period of President Houari Boumediene's rule witnessed significant development in the field of culture and arts, thanks to the capabilities and means of communication provided by the state, which played a role in portraying scenes and highlighting cultural awareness. These means created values and expressed identity and nationalism, and were a powerful factor in asserting oneself and defending rights. The media managed the cultural aspect in a distinguished manner, strengthening the Algerian personality. It is a cultural struggle with its capabilities and expertise, reflecting the continuous development and efforts made by the state